Determinan Tax Effort pada Pemerintah Kabupaten/Kota di Provinsi Sumatera Selatan - Intan Yuriska; Faridah; Muhammad Husni Mubarok (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to ascertain how tax effort in South Sumatra Province's regency and city governments is impacted by general allocation funds, special allocation funds, revenue sharing funds, and regional spending. This study is quantitative and uses secondary data from the Supreme Audit Agency's official website (www.bpk.go.id). From 2018 to 2022, 17 regencies and cities in the South Sumatra Province served as the study's population. A non-probability sampling procedure with a saturated sample type was utilized for the sample selection, resulting in a total of 85 samples. The study's findings suggest that regional spending, revenue sharing funds, special allocation funds, and general allocation funds all have a favorable and substantial impact on tax effort.